2003
DOI: 10.1021/ol034886y
|View full text |Cite
|
Sign up to set email alerts
|

Concise and Highly Stereocontrolled Synthesis of 1-Deoxygalactonojirimycin and Its Congeners Using Dioxanylpiperidene, a Promising Chiral Building Block

Abstract: [reaction: see text] A concise and stereoselective synthesis of the chiral building block, dioxanylpiperidene 4 as a precursor for deoxyazasugars, starting from the Garner aldehyde 5 using catalytic ring-closing metathesis (RCM) for the construction of the piperidine ring is described. The asymmetric synthesis of 1-deoxygalactonojirimycin and its congeners 1-3 was carried out via the use of 4 in a highly stereocontrolled mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 19 publications
(10 reference statements)
1
26
0
Order By: Relevance
“…[67] Other methods to acquire syn alcohols as the major products by addition of vinyllithium [68] (generated in situ from tetravinyltin and methyllithium) and zinc bromide on Garner aldehyde were not suitable for scaling-up purposes, due to the lower stabilities of the reagents. Diastereomerically pure allylic alcohols 16 a-d were converted into their corresponding MOM ethers 17 a-d by treatment with MOM chloride in quantitative yields.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[67] Other methods to acquire syn alcohols as the major products by addition of vinyllithium [68] (generated in situ from tetravinyltin and methyllithium) and zinc bromide on Garner aldehyde were not suitable for scaling-up purposes, due to the lower stabilities of the reagents. Diastereomerically pure allylic alcohols 16 a-d were converted into their corresponding MOM ethers 17 a-d by treatment with MOM chloride in quantitative yields.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The known acetal 6 [9], readily available from L-serine, was treated with p-toluenesulfonic acid in methanol to give the diol which, without further purification, was selectively silylated with tert-butyldimethylsilyl chloride to afford silyl ether 7 in 71% yield from 6. After protection of the secondary hydroxyl group, the resulting methoxymethyl ether 8 was converted to the primary alcohol 9 by deprotection of a silyl group with TBAF (tetrabutylammonium fluoride).…”
Section: Resultsmentioning
confidence: 99%
“…A synthesis of fagomine 18 and analogs 19 and 20, [63] as well as DGJ (11) and analogs 70 and 144 [64] from d-Garner's aldehyde (derived from d-serine) with a ring-closing metathesis (RCM) as the key step has been reported by Takahata et al, as shown in Schemes 16-19. In the last decade, the RCM reaction [65] has emerged as an extraordinarily powerful and general method for the construction of nitrogen heterocyclic compounds and has relevant application in the field of alkaloid synthesis.…”
Section: Chiral-pool Starting Materials: Amino Acidsmentioning
confidence: 99%
“…To demonstrate the efficiency of this approach to azasugars, the same authors described the synthesis of DGJ (11) and its congeners [64] 70 and 144 relying, in the first step, on the addition of a vinyl metal reagent to d-Garner's aldehyde (see Scheme 18 and 19).…”
Section: Chiral-pool Starting Materials: Amino Acidsmentioning
confidence: 99%